Nutritional status and gastrointestinal issues in school-aged children with autism spectrum disorder - Lismary N. García-Muñoz (2025)
The relationship between gastrointestinal alterations and the characteristics of children with autism spectrum disorders highlights the importance of a nutritional approach in their multidisciplinary care. The objective of this research was to determine the relationship between nutritional profiles and gastrointestinal alterations. This descriptive, correlational, and cross- sectional study evaluated 55 school-aged children with autism. The nutritional profile was determined using the anthropometric indicator body mass index for age (BMI/age). The dietaryassessment included a record of macronutrient, gluten, and casein intake. The clinical evaluation included signs of gastrointestinal alterations and malnutrition. Anthropometric results showed that 63.6% of the children were within the normal range, 1.8 % were underweight, and 34.5 % were overweight. The most frequent gastrointestinal alterations were foul-smelling flatulence, constipation, abdominal pain, and distension. No relationship was found between gastrointestinal alterations and anthropometric diagnosis or macronutrient intake. However, a statistically significant positive relationship (p<0.01) was found between gastrointestinal alterations and clinical signs of nutritional deficiencies, gluten consumption, and the degree of autism. Additionally, a positive trend was observed between gastrointestinal alterations and casein consumption. In conclusion, the consumption of gluten- and casein-containing foods directly affects gastrointestinal alterations and, in turn, the severity of autism in children. These findings underscore the need for early nutritional intervention as an effective strategy to improve symptoms associated with autism.